Effects of dry needling on vertical jump performance in female volleyball players. A randomized controlled trial - Ladriñán-Maestro, Arturo; Sánchez-Infante, Jorge; Martín-Vera, Daniel; Del-Blanco-Múñiz, Jose Angel; Domínguez-Balmaseda, Diego; Guzmán-Pavón, María José; Sánchez-Sierra, Alberto (Frontiers in Sports and Active Living, 2024)
Introduction Injury prevention and performance enhancement are paramount goals in sports. Myofascial Pain Syndrome, primarily caused by myofascial trigger points, can result in referred pain, stiffness, muscle shortening, and weakness. This study aimed to assess the impact of dry needling (DN) on latent myofascial trigger points on vertical jump performance in female volleyball players. Methods A single-blind, randomized controlled clinical trial was conducted with twenty-six healthy female volleyball players who had no lower limb injuries in the last six months, exhibited latent trigger points in the triceps surae muscles, and were familiar with the countermovement jump test. Participants were randomly assigned to either a control group or an experimental group (which received a single DN session). Vertical jump performance variables, including jump height as the primary outcome, were assessed using a force platform at five time points: before the intervention, immediately post-treatment, 24 h post-treatment, 72 h post-treatment, and one-week post-intervention. Results The experimental group showed significantly lower values for vertical jump height, flight time, velocity, strength, and power immediately after the needling intervention (p < 0.05). However, these values were significantly higher one-week post-intervention across all variables (p < 0.01). These findings indicate that DN initially decreases jumping performance, but improvements are observed one week after the intervention. In the comparison between groups, the experimental group exhibited higher values at the one-week follow-up for vertical jump height, flight time, speed, and power compared to the control group (p < 0.05). Conclusions DN appears to be an effective technique for improving vertical jump performance in female volleyball players one week after its application. Clinical Trial Registration ClinicalTrials.gov, identifier (NCT06184672).